Suits. Season three [videorecording (DVD)] - Torres, Gina; Macht, Gabriel, 1972-; Adams, Patrick J., 1981- (Universal Studios Home Entertainment, 2014)
Power is shifting and lines are crossed in the gripping third season. Following the firm's merger with a prestigious British business, loyalties are tested between high-powered counsel Harvey Specter, legal prodigy Mike Ross, and their boss, managing partner Jessica Pearson.